Effect of the impeller blade outlet setting angle on the performance of the helical axial-flow multiphase pump - Wang, Jiaqiong; Hu, Chen; Bai, Ling; Agarwal, Ramesh; Zhou, Ling (Frontiers in Energy Research, 2024)
As one of the core equipment of the multiphase mixing system, the helical axial-flow multiphase pump plays a vital role in the process of offshore oil extraction. In order to explore the influence of impeller blade outlet setting angle on the internal flow of helical axial-flow multiphase pump, this paper, on the basis of the original multiphase pump, increases the outlet setting angle of the flow surface by -3°, -1.5°, and 1.5° respectively, and calculates the flow characteristics of the impeller with four different outlet setting angles (including the original impeller) under the design condition with different inlet gas volume fraction (GVF =0, 10%, 30%，50%, and 70%) by adopting Euler-Euler non-homogeneous flow model and SST k-ω turbulence model, and compare its external characteristic curve and higher inlet GVF conditions (50%) impeller and guide vane internal pressure, velocity, gas distribution and other rules of change. The results show that: in the pure water state, increasing the outlet setting angle appropriately can enhance both the pressure pressurization capability and efficiency of the helical axial-flow multiphase pump; the pressure pressurization capability and efficiency of each scheme decrease with the increase of inlet GVF, and at 50%-70% inlet GVF, the option of increasing the outlet setting angle by -1.5° is better; as the blade outlet setting angle decreases, the axial cross-sectional pressure after gas-liquid mixing increases, the overall velocity distribution is more uniform, and the vortex formed due to the counter-pressure flow in the secondary guide vane is reduced; the accumulation of gas phase on the backside of the impeller and guide vanes improves, leading to a reduction in flow losses.